2020
DOI: 10.15381/rivep.v31i2.17822
|View full text |Cite
|
Sign up to set email alerts
|

Estado de inmunidad humoral posvacunal de caninos y felinos en un foco de rabia canina de origen silvestre de una región de Colombia

Abstract: El objetivo de la investigación fue determinar la respuesta posvacunal de caninos y felinos del municipio de San Sebastián de Mariquita, Colombia, que presentó en 2014 un caso fatal de rabia canina por variante atípica de murciélago. Se realizó un muestreo por conveniencia, de corte transversal y no experimental a 130 caninos y 38 felinos de la zona rural y urbana del municipio citado. Se tomaron muestras de sangre y para la titulación de anticuerpos antirrábicos se utilizó un kit de ELISA (Platelia Rabies II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…found the opposite association—that is, higher antibody titers in younger dogs. 26 Our results might be due to higher antibody titers associated with multiple rabies boosters in older dogs and older dogs being more likely to have received at least one vaccine. This finding highlights the effects of population turnover on decreased herd immunity and the importance of boosters in young adult animals to achieve real long-lasting immunity.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…found the opposite association—that is, higher antibody titers in younger dogs. 26 Our results might be due to higher antibody titers associated with multiple rabies boosters in older dogs and older dogs being more likely to have received at least one vaccine. This finding highlights the effects of population turnover on decreased herd immunity and the importance of boosters in young adult animals to achieve real long-lasting immunity.…”
Section: Discussionmentioning
confidence: 77%
“…Another study evaluated the number of vaccine boosters and found that dogs that were vaccinated for 3 consecutive years had adequate titers. 26 It is possible that dogs in our study had not been vaccinated for more than 3 years or were subjects to irregular (not annual) vaccination previous to their last vaccine. Thus, their immunological status not only represents the time since last vaccination but inconsistent vaccination.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations